2022
DOI: 10.3390/plants11202761
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Enzymatic Hydrolysed L-α-Amino Acid Based Biostimulant to Improve Sunflower Tolerance to Imazamox

Abstract: Herbicides, commonly used in agriculture to control weeds, often cause negative effects on crops. Safeners are applied to reduce the damage to crops without affecting the effectiveness of herbicides against weeds. Plant biostimulants have the potential to increase tolerance to a series of abiotic stresses, but very limited information exists about their effects on herbicide-stressed plants. This study aims to verify whether the application of a potential safener such as Terra-Sorb®, an L-α-amino acid-based bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…How biostimulants can improve crop stress tolerance from herbicides has been tested by many researchers. Balavanova et al [18] and Navarro-León et al [17] evaluated the effect of an amino acid compound in a tank mixture with imazamox on sunflower tolerance to the particular herbicide. Balabanova et al [18] found that this combination provided an increase in fresh weight, plant height, and leaf area of the sunflowers after 14 days from the application compared to sunflowers that only imazamox was applied, proving that biostimulants potentially can be used as an ameliorative application.…”
Section: Effect Of Biostimulants On Mitigating Stress From Herbicidal...mentioning
confidence: 99%
See 2 more Smart Citations
“…How biostimulants can improve crop stress tolerance from herbicides has been tested by many researchers. Balavanova et al [18] and Navarro-León et al [17] evaluated the effect of an amino acid compound in a tank mixture with imazamox on sunflower tolerance to the particular herbicide. Balabanova et al [18] found that this combination provided an increase in fresh weight, plant height, and leaf area of the sunflowers after 14 days from the application compared to sunflowers that only imazamox was applied, proving that biostimulants potentially can be used as an ameliorative application.…”
Section: Effect Of Biostimulants On Mitigating Stress From Herbicidal...mentioning
confidence: 99%
“…The use of herbicides could cause injuries to the crops, depending on the active ingredient of the herbicide, the application rate and time, and the method of the application [16]. For this reason, it is very common for agricultural practice to use some compounds called herbicide safeners in order to minimize the injury that herbicides cause to the crops [16] without affecting the efficacy of the herbicides [17]. Many biostimulants have the potential to induce plant tolerance to different types of abiotic stresses [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantageous factor of the accumulation of various forms of microbes employed as plant biofertilizers may hinge upon their potentiality under unfavorable conditions of the environments. Studies have revealed the activity of biostimulants when different materials were added together, describing synergistic interactions (Montoneri et al, 2022;Navarro-Leoń et al, 2022;Canellas et al, 2023). This review portrays how biostimulants (microbial-based) can be produced employing the following methods: AMF/PGPR multispecies consortia, a single PGPM strain, and aggregation of PGPMs with inorganic and organic chemicals.…”
Section: Synergistic Response Of Microbial Biostimulant Componentsmentioning
confidence: 99%
“…The phytotoxic effect could perhaps be reduced using some biostimulants. L-α-amino acid-based biostimulants show a protective effect against the stress caused by the application of the imazamox herbicide in sunflower plants, followed by the protection of the photosynthetic activity and reduction in the oxidative stress in the plant [ 12 ]. Furthermore, even some strains of entomopathogenic fungi can act as biostimulants for some crops by their ability to infect insect pests and to promote plant growth.…”
mentioning
confidence: 99%